Measurements of the branching fraction ratio B(ϕ → μ+μ−)/B(ϕ → e+e−) with charm meson decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Cocha Toapaxi, Carlos; De Cian, Michel; Frau, Giulia; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Herrero Gascón, Paula; et al. (Journal of high energy physics, 2024)
Measurements of the branching fraction ratio B(ϕ → μ+μ−)/B(ϕ → e+e−) with D+s → π+ϕ and D+ → π+ϕ decays, denoted Rs ϕπ and Rd ϕπ, are presented. The analysis is performed using a dataset corresponding to an integrated luminosity of 5.4 fb−1 of pp collision data collected with the LHCb experiment. The branching fractions are normalised with respect to the B+ → K+J/ψ(→ e+e−) and B+ → K+J/ψ(→ μ+μ−) decay modes. The combination of the results yields Rϕπ = 1.022 ± 0.012 (stat) ± 0.048 (syst). The result is compatible with previous measurements of the ϕ → ℓ+ℓ− branching fractions and predictions based on the Standard Model.
Im Titel erscheinen die Zeichen + und - tiefgestellt
Gesehen am 05.05.2025
LHCb Collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, C.E. Cocha Toapaxi, M. De Cian, G. Frau, F. Glaser, P.A. Günther, X. Han, S. Hansmann-Menzemer, P. Herrero Gascon, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, S. Roy, M. Ruiz Diaz, G. Tuci, L.H. Ueckert, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und 1078 weitere]